Components of Elitizing Educational and Pedagogical Environment of Higher School - N B Karabuschenko; T S Pilishvili; T V Chkhikvadze (Peoples' Friendship University of Russia (RUDN University), 2014)
The need of creating an elitilizing educational and pedagogical environment of the university is substantiated in the paper. There are analyzed such equal ranking components as psycho-didactic, educational, spatially-material, social, psycho-physiological, cultural-aesthetic, creative activity-based, worldview components.